Perkembangan Agama Islam di Indonesia Pasca Kemerdekaan - Efi Susilawati; Heri Kurnia (Innovations in Multidisciplinary Education Journal, 2024)
This study aims to determine the development of Islam in Indonesia after independence shows significant dynamics. Since Indonesia's independence in 1945, Islam has undergone transformation in social, political, and cultural aspects. According to data from the Ministry of Religion of the Republic of Indonesia, the number of Muslims in Indonesia is estimated to reach 227 million in 2021, making it the country with the largest Muslim population in the world. One important finding is the strengthening of the role of Islamic organizations in social and political life. Organizations such as Nahdlatul Ulama (NU) and Muhammadiyah play a key role in spreading moderate and tolerant Islamic values. NU, for example, has contributed to the development of education and social in various regions, while Muhammadiyah is active in the fields of health and education. Statistics show that more than 30 million NU members and around 29 million Muhammadiyah members are involved in various social and humanitarian activities.